MUSTIC 2023 Conference Proceedings - Editor-in-Chief (African Journal of Science, Technology and Social Sciences, 2023)
Dear Reader, Welcome to the MUSTIC 2023 Conference Proceedings, a compilation that echoes the diverse and impactful discussions held during this year’s Meru University of Science and Technology International Conference. Themed "SDGsfor Development: Leveraging Interlinkages among the SDGs to Realize the 2030 Agenda through Research and Innovation in the Post Covid Era,” this conference has been a crucible of ideas, insights, and innovations. Within these pages, you will find a condensed reflection of the intellectual richness explored across nine thought-provoking sub-themes. From Agriculture, Food Security, Safety, and Bio-security to the Reimagining of Pure and Applied Sciences for the Post Pandemic Future, each abstract encapsulates the essence of scholarly endeavors dedicated to addressing the intricate challenges of our time. MUSTIC 2023 has fostered interdisciplinary dialogue, bringing together experts from various fields to share their research and pave the way for sustainable development. As we present this compendium, we invite you to delve into the abstracts, each a snapshot of the groundbreaking work that contributes to a resilient and sustainable future. Some selected papers will also be published in the upcoming issue of the AJSTSS (Vol 2 Issue 2). As we navigate the ever-expanding frontiers of knowledge, we invite you to engage with the wealth of information provided by AJSTSS. We extend our gratitude to the contributors, reviewers, and readers who make this scholarly endeavor possible. Welcome to a world of discovery! Best regards, Prof. Eric Muchiri (Ph.D.) Editor-in-Chief - African Journal of Science Technology and Social Sciences